Preparation method of aluminum silicate nanofiber / acrylamide-sodium acrylate copolymer composite aerogel

By modifying aluminum silicate nanofibers and cross-linking copolymerization with acrylamide-sodium acrylate copolymer, composite aerogels are generated, which solves the problems of insufficient adsorption capacity of aluminum silicate nanofibers on heavy metal ions and difficulty in recycling, and achieves efficient adsorption and environmentally friendly adsorption materials.

CN119455919BActive Publication Date: 2025-04-18CHANGSHU INSTITUTE OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510045701.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-18
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

The aluminum silicate nanofiber has limited adsorption capacity to heavy metal ions, and its small size makes recycling difficult, increasing inconvenience and environmental risks in practical applications.

Method used

The aluminum silicate nanofibers are treated by modification such as aminolation and double bond introduction, and are cross-linked and copolymerized with acrylamide-sodium acrylate copolymer to form a composite aerogel to form a stable crosslinked structure to improve adsorption performance.

Benefits of technology

The adsorption amount of heavy metal ions is significantly increased, and the recovery problem of aluminum silicate nanofibers is solved by forming a water-insoluble composite aerogel, reducing the potential impact on the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455919B_ABST
    Figure CN119455919B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing an aluminum silicate nanofiber / acrylamide-sodium acrylate copolymer composite aerogel, comprising the following steps: modifying the aluminum silicate nanofiber by an aminosilane coupling agent to obtain an amination aluminum silicate nanofiber; subjecting the amination aluminum silicate nanofiber to a substitution reaction of amino and chloroolefin to introduce a double bond on the surface of the amination aluminum silicate nanofiber; using the amination aluminum silicate nanofiber with the double bond introduced as a crosslinking agent, acrylamide and acrylic acid as monomers, and after a crosslinking copolymerization reaction by a solution polymerization method, the reaction solution is freeze-dried to obtain an aluminum silicate nanofiber / acrylamide-sodium acrylate copolymer composite aerogel. The invention improves the adsorption capacity of heavy metal ions, is easy to recycle, and has excellent durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a composite aerogel, in particular to a method for preparing an aluminum silicate nanofiber / acrylamide-sodium acrylate copolymer composite aerogel. Background Art

[0002] The discharge of industrial wastewater contaminated by heavy metal ions can cause environmental problems. As an environmentally friendly inorganic nanomaterial, aluminum silicate nanofibers have the characteristics of high specific surface area and therefore have a certain adsorption capacity. However, the adsorption capacity of aluminum silicate nanofibers for heavy metal ions is relatively limited, mainly relying on physical adsorption on its surface and limited chemical action sites, which limits its application in efficient heavy metal removal. In addition, the small size of aluminum silicate nanofibers makes it difficult to separate and recover them after treatment, increasing the inconvenience and environmental risks in practical applications. Summary of the invention

[0003] In view of the above-mentioned defects of the prior art, the present invention provides a method for preparing aluminum silicate nanofiber / acrylamide-sodium acrylate copolymer composite aerogel, which improves the adsorption capacity of heavy metal ions and makes the aluminum silicate nanofiber easy to recycle.

[0004] The technical solution of the present invention is as follows: A method for preparing aluminum silicate nanofiber / acrylamide-sodium acrylate copolymer composite aerogel comprises the following steps:

[0005] (1) Modifying aluminum silicate nanofibers by using an aminosilane coupling agent to obtain amino-modified aluminum silicate nanofibers;

[0006] (2) subjecting the amino-aluminum silicate nanofibers to a substitution reaction between amino groups and chloroolefins, thereby introducing double bonds on the surface of the amino-aluminum silicate nanofibers;

[0007] (3) Using amino-modified aluminum silicate nanofibers with double bonds as crosslinking agents, acrylamide and acrylic acid as monomers, a crosslinking copolymerization reaction was carried out by solution polymerization, and then the reaction solution was freeze-dried to obtain aluminum silicate nanofiber / acrylamide-sodium acrylate copolymer composite aerogel.

[0008] Furthermore, the step (1) is to disperse the aluminum silicate nanofibers in a mixture of ethanol and water, and after uniform ultrasonic dispersion, add an aminosilane coupling agent for stirring reaction, wherein the mass ratio of the aluminum silicate nanofibers to the aminosilane coupling agent is 1:(0.1-0.5).

[0009] Furthermore, the stirring reaction in step (1) is carried out at 60-90° C. for 8-12 hours.

[0010] Furthermore, the aminosilane coupling agent is one of 3-aminopropyltrimethoxysilane and 3-aminopropyltriethoxysilane.

[0011] Furthermore, in the step (2), the amino aluminum silicate nanofibers are dispersed in acetonitrile under a nitrogen atmosphere, ultrasonically dispersed uniformly, and chloroolefins and an acid binding agent are added to carry out a substitution reaction, wherein the mass ratio of the amino aluminum silicate nanofibers, the chloroolefins and the acid binding agent is 1:(1~2):(1~2), and the acid binding agent is preferably pyridine.

[0012] Furthermore, the substitution reaction in step (2) is carried out at 70-90° C. for 8-12 hours.

[0013] Furthermore, the chloroolefin is an allylic chloroolefin, preferably 3-chloropropene.

[0014] Furthermore, the step (3) is to ultrasonically disperse the amino-aluminum silicate nanofibers with double bonds introduced in deionized water, add acrylamide and acrylic acid monomers in sequence, adjust the solution pH to 9-10 by NaOH, and finally add an initiator to carry out a cross-linking copolymerization reaction, wherein the mass ratio of the amino-aluminum silicate nanofibers with double bonds introduced, acrylamide, acrylic acid, and initiator is 1: (7-10): (3-7): (0.1-0.3), and the initiator is one of ammonium persulfate and potassium persulfate.

[0015] Furthermore, the cross-linking copolymerization reaction in step (3) is carried out under nitrogen protection at 40-60° C. for 6-10 hours.

[0016] Furthermore, the freeze drying in step (3) is to freeze dry the reaction solution at -50 to -40°C for 20 to 40 hours.

[0017] The advantages of the present invention compared with the prior art are:

[0018] The invention further introduces double bonds through a substitution reaction between amino groups and chloroolefins on the basis of amination of aluminum silicate nanofibers, and then crosslinks and polymerizes between aluminum silicate nanofibers to generate a copolymer of sodium acrylate and acrylamide, thereby fully forming an effective crosslinking structure, integrating the rich active functional groups (amide groups, anionic groups (-COO - )) and the structural characteristics of aluminum silicate nanofibers achieve a strong combination and synergistic enhancement of the three in adsorption performance, significantly improving its adsorption capacity for heavy metal ions.

[0019] The present invention generates a copolymer composite aerogel of sodium acrylate and acrylamide containing aluminum silicate nanofibers, which is insoluble in water, avoids the problem of complex post-treatment required for adsorption using polyacrylamide and polyacrylic acid, and also solves the problem of difficulty in recycling aluminum silicate nanofibers. The composite aerogel does not release harmful substances during use, thereby reducing potential impact on the environment.

[0020] The composite aerogel prepared by the present invention has a stable cross-linked structure, so that the composite aerogel can maintain its structural integrity and performance stability during the recycling process, thereby improving the durability of the adsorption material. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The adsorption capacity of the aluminum silicate nanofiber / acrylamide-sodium acrylate copolymer composite aerogel prepared in Example 1 of the present invention for lead ions changes with the number of cycles. DETAILED DESCRIPTION

[0022] The present invention will be further described below in conjunction with the embodiments, but are not intended to limit the present invention.

[0023] Example 1

[0024] A method for preparing aluminum silicate nanofiber / acrylamide-sodium acrylate copolymer composite aerogel comprises the following steps:

[0025] (1) 1 g of aluminum silicate nanofibers was dispersed in a mixture of 95% ethanol and water, and after being uniformly dispersed by ultrasonication, 0.1 g of 3-aminopropyltrimethoxysilane was added, and the reaction solution was stirred at 60°C for 12 h. After the reaction, the mixture was filtered, washed with deionized water, and dried to obtain amino aluminum silicate nanofibers; the aluminum silicate nanofibers were sourced from Shanghai MacLean Biochemical Technology Co., Ltd., CAS: 1327-36-2, and the aluminum silicate nanofibers used below were from the same source;

[0026] (2) Under nitrogen atmosphere, 1 g of the above-mentioned amino-aluminum silicate nanofibers was dispersed in acetonitrile and dispersed evenly by ultrasonication. 1 g of 3-chloropropylene and 1 g of pyridine were added. The reaction solution was reacted at 70° C. for 12 h, and then distilled under reduced pressure. The amino-aluminum silicate nanofibers rich in double bonds were obtained after being fully washed with ethanol and dried.

[0027] (3) 1 g of the above-mentioned amino-modified aluminum silicate nanofibers rich in double bonds was ultrasonically dispersed in deionized water, and 7 g of acrylamide and 3 g of acrylic acid monomer were added in sequence. Then, NaOH was added to adjust the pH of the solution to 9 to convert acrylic acid into sodium acrylate. Finally, 0.1 g of ammonium persulfate was added and stirred for 10 h at 40 ° C under nitrogen protection. The reaction solution was freeze-dried at -40 ° C for 40 h to obtain aluminum silicate nanofiber / acrylamide-sodium acrylate copolymer composite aerogel.

[0028] The adsorption performance test experiment of the aluminum silicate nanofiber / acrylamide-sodium acrylate copolymer composite aerogel of this Example 1 is as follows:

[0029] Prepare 100 mL of an aqueous solution with a lead ion concentration of 100 mg / L (lead nitrate as a reagent) in a flask, adjust the solution pH to 7 with 0.1 M NaOH, add the prepared aluminum silicate nanofiber / acrylamide-sodium acrylate copolymer composite aerogel, and then adsorb for 3 hours at 200 rpm in a constant temperature oscillator at 30 ° C. After adsorption, take the upper clear liquid, and use ICP-OES to determine the concentration of lead ions in the clear liquid. The adsorption amount of lead ions by the adsorbent material is calculated by the following formula ( Q , mg / g), and the results are listed in Table 1.

[0030] Q =( C 0 - C t ) V / M

[0031] Q is the adsorption amount (g / g); C 0 is the initial concentration of heavy metal ions (mg / L); C t is the concentration of heavy metal ions after adsorption (mg / L); V is the volume of the solution (L); M is the mass of the adsorbent (mg).

[0032] The cyclic performance test experiment of the aluminum silicate nanofiber / acrylamide-sodium acrylate copolymer composite aerogel of this embodiment 1 is as follows:

[0033] The aluminum silicate nanofiber / acrylamide-sodium acrylate copolymer composite aerogel saturated with lead ions was rinsed with deionized water for 3 times, then immersed in 100 mL of 1 mol / L ethylenediaminetetraacetic acid solution, and desorbed at 300 rpm in a constant temperature oscillator at 30°C for 5 hours. The sample was then taken out and rinsed with deionized water for 3 times again, and then dried before the next adsorption. Each adsorption and desorption was regarded as 1 cycle, and the change in the adsorption amount of lead ions by the sample with the number of cycles was recorded to judge the reusability of the sample. The results of Example 1 are shown in FIG. Figure 1 As shown in the figure, it can be seen that with the increase in the number of cycles, the adsorption capacity of lead ions by the prepared aerogel only shows a slight decrease. After 6 cycles, it still maintains excellent adsorption capacity, and the adsorption capacity of lead ions can still reach 94% of the initial adsorption capacity. This result strongly proves that the covalent cross-linking modification technology adopted by the present invention can effectively maintain the structural integrity and performance stability of the aerogel during the cycle, thereby significantly improving the durability of the material.

[0034] Example 2

[0035] (1) Disperse 1 g of aluminum silicate nanofibers in a mixture of 95% ethanol and water, and after uniform ultrasonic dispersion, add 0.3 g of 3-aminopropyltriethoxysilane, and stir the reaction solution at 75°C for 10 h. After the reaction is completed, filter, wash with deionized water, and dry to obtain amino aluminum silicate nanofibers;

[0036] (2) Under nitrogen atmosphere, 1 g of the above-mentioned amino aluminum silicate nanofibers was dispersed in acetonitrile and dispersed evenly by ultrasonication. 1.5 g of 3-chloropropylene and 1.5 g of pyridine were added. The reaction solution was reacted at 80° C. for 10 h, and then distilled under reduced pressure. The amino aluminum silicate nanofibers rich in double bonds were obtained after being fully washed with ethanol and dried.

[0037] (3) 1 g of the above-mentioned amino-modified aluminum silicate nanofibers rich in double bonds was ultrasonically dispersed in deionized water, and 8.5 g of acrylamide and 5 g of acrylic acid monomer were added in sequence, and then NaOH was added to adjust the pH of the solution to 9.5 to convert acrylic acid into sodium acrylate. Finally, 0.2 g of potassium persulfate was added, and the mixture was stirred and reacted at 50°C for 8 h under nitrogen protection. The reaction solution was freeze-dried at -45°C for 30 h to obtain an aluminum silicate nanofiber / acrylamide-sodium acrylate copolymer composite aerogel, and its adsorption performance was measured according to the adsorption performance experiment of the product in Example 1. The results are listed in Table 1.

[0038] Example 3

[0039] (1) Dispersing 1 g of aluminum silicate nanofibers in a mixture of 95% ethanol and water, and after uniform ultrasonic dispersion, adding 0.5 g of 3-aminopropyltriethoxysilane, stirring the reaction solution at 90°C for 8 h, and after the reaction is completed, filtering, washing with deionized water, and drying to obtain amino aluminum silicate nanofibers;

[0040] (2) Under nitrogen atmosphere, 1 g of the above-mentioned amino aluminum silicate nanofibers was dispersed in acetonitrile and dispersed evenly by ultrasonication. 2 g of 3-chloropropylene and 2 g of pyridine were added. The reaction solution was reacted at 90° C. for 8 h, and then distilled under reduced pressure. The amino aluminum silicate nanofibers rich in double bonds were obtained after being fully washed with ethanol and dried.

[0041] (3) 1 g of the above-mentioned amino-modified aluminum silicate nanofibers rich in double bonds was ultrasonically dispersed in deionized water, and 10 g of acrylamide and 7 g of acrylic acid monomer were added in sequence, and then NaOH was added to adjust the pH of the solution to 10 to convert acrylic acid into sodium acrylate. Finally, 0.3 g of potassium persulfate was added, and the mixture was stirred and reacted at 60°C for 6 h under nitrogen protection. The reaction solution was freeze-dried at -50°C for 20 h to obtain an aluminum silicate nanofiber / acrylamide-sodium acrylate copolymer composite aerogel, and its adsorption performance was measured according to the adsorption performance experiment of the product in Example 1. The results are listed in Table 1.

[0042] Comparative Example 1

[0043] 10 g of acrylamide monomer was added to deionized water, and then 0.1 g of ammonium persulfate was added, and the mixture was stirred and reacted for 10 h at 40° C. under nitrogen protection. The reaction solution was freeze-dried at -40° C. for 40 h to obtain polyacrylamide aerogel, and its adsorption performance was measured according to the adsorption performance experiment of the product in Example 1, and the results are listed in Table 1.

[0044] Comparative Example 2

[0045] 7 g of acrylamide and 3 g of acrylic acid monomer were added to deionized water, and then NaOH was added to adjust the solution pH to 9 to convert acrylic acid into sodium acrylate. Finally, 0.1 g of ammonium persulfate was added and stirred for reaction at 40° C. under nitrogen protection for 10 h. The reaction solution was freeze-dried at -40° C. for 40 h to obtain acrylamide-sodium acrylate copolymer aerogel, and its adsorption performance was measured according to the adsorption performance experiment of the product in Example 1, and the results are listed in Table 1.

[0046] Comparative Example 3

[0047] 1g of aluminum silicate nanofibers was ultrasonically dispersed in deionized water, and 7g of acrylamide and 3g of acrylic acid monomer were added in sequence, and then NaOH was added to adjust the pH of the solution to 9, so that acrylic acid was converted into sodium acrylate, and finally 0.1g of ammonium persulfate was added, and the reaction was stirred at 40°C for 10h under nitrogen protection. The reaction solution was freeze-dried at -40°C for 40h to obtain an aluminum silicate nanofiber / acrylamide-sodium acrylate copolymer composite aerogel, and its adsorption performance was measured according to the adsorption performance experiment of the product in Example 1, and the results are listed in Table 1.

[0048] Table 1 Adsorption amount of lead ions by aerogels prepared in Examples 1-3 and Comparative Examples 1-3

[0049]

[0050] By comparing and analyzing the adsorption results of the embodiment and comparative examples 1 and 2, it can be seen that the aluminum silicate nanofiber / acrylamide-sodium acrylate copolymer composite aerogel prepared in the embodiment combines the rich active functional groups of polyacrylamide and sodium polyacrylate with the unique physical and chemical properties of aluminum silicate nanofiber, realizing the strong combination and synergistic enhancement of the three in adsorption performance, and giving the aerogel excellent adsorption performance for lead ions. In the aerogel prepared in comparative example 3, an effective cross-linking structure cannot be formed between the aluminum silicate nanofiber and the acrylamide-sodium acrylate copolymer, resulting in a weak interaction force between them, and the potential for synergistic enhancement cannot be fully demonstrated. The composite aerogel in the embodiment, by forming a stable cross-linking structure, enables the aluminum silicate nanofiber and the acrylamide-sodium acrylate copolymer to be closely combined together, giving full play to their synergistic adsorption synergistic effect. In addition, more amine groups are introduced in the cross-linking process, further improving the adsorption performance of the composite aerogel for heavy metal ions. Therefore, the aerogel prepared in comparative example 3 is not as good as the composite aerogel prepared in the embodiment in terms of heavy metal ion adsorption performance.

Claims

1. A method for preparing aluminum silicate nanofiber / acrylamide-sodium acrylate copolymer composite aerogel, characterized in that: The following steps are involved: (1) Modifying aluminum silicate nanofibers by using an aminosilane coupling agent to obtain amino-modified aluminum silicate nanofibers; (2) subjecting the amino-aluminum silicate nanofibers to a substitution reaction between amino groups and chloroolefins, thereby introducing double bonds on the surface of the amino-aluminum silicate nanofibers; (3) Using amino-silica aluminum nanofibers with double bonds as crosslinking agents, acrylamide and acrylic acid as monomers, a crosslinking copolymerization reaction is carried out by solution polymerization. Specifically, the amino-silica aluminum nanofibers with double bonds are ultrasonically dispersed in deionized water, acrylamide and acrylic acid monomers are added in sequence, the pH of the solution is adjusted to 9-10 by NaOH, and finally an initiator is added to carry out a crosslinking copolymerization reaction. After the crosslinking copolymerization reaction, the reaction solution is freeze-dried to obtain an aluminum silicate nanofiber / acrylamide-sodium acrylate copolymer composite aerogel.

2. The method for preparing the aluminum silicate nanofiber / acrylamide-sodium acrylate copolymer composite aerogel according to claim 1, characterized in that: The step (1) is to disperse the aluminum silicate nanofibers in a mixture of ethanol and water, and after uniform ultrasonic dispersion, add an aminosilane coupling agent for stirring reaction, wherein the mass ratio of the aluminum silicate nanofibers to the aminosilane coupling agent is 1:(0.1-0.5).

3. The method for preparing the aluminum silicate nanofiber / acrylamide-sodium acrylate copolymer composite aerogel according to claim 2, characterized in that: The stirring reaction in step (1) is carried out at 60-90° C. for 8-12 hours.

4. The method for preparing the aluminum silicate nanofiber / acrylamide-sodium acrylate copolymer composite aerogel according to claim 2, characterized in that: The aminosilane coupling agent is one of 3-aminopropyltrimethoxysilane and 3-aminopropyltriethoxysilane.

5. The method for preparing the aluminum silicate nanofiber / acrylamide-sodium acrylate copolymer composite aerogel according to claim 1, characterized in that: In the step (2), the amino aluminum silicate nanofibers are dispersed in acetonitrile under a nitrogen atmosphere, ultrasonically dispersed evenly, and chloroolefins and an acid binding agent are added to carry out a substitution reaction, wherein the mass ratio of the amino aluminum silicate nanofibers, the chloroolefins and the acid binding agent is 1:(1-2):(1-2).

6. The method for preparing the aluminum silicate nanofiber / acrylamide-sodium acrylate copolymer composite aerogel according to claim 5, characterized in that: The substitution reaction in step (2) is carried out at 70-90° C. for 8-12 hours.

7. The method for preparing the aluminum silicate nanofiber / acrylamide-sodium acrylate copolymer composite aerogel according to claim 5, characterized in that: The chloroolefin is an allylic chloroolefin.

8. The method for preparing aluminum silicate nanofiber / acrylamide-sodium acrylate copolymer composite aerogel according to claim 1, characterized in that: In the step (3), the mass ratio of the amino-silicon aluminum nanofibers, acrylamide, acrylic acid, and initiator into which double bonds are introduced is 1:(7-10):(3-7):(0.1-0.3).

9. The method for preparing the aluminum silicate nanofiber / acrylamide-sodium acrylate copolymer composite aerogel according to claim 8, characterized in that: The cross-linking copolymerization reaction in step (3) is carried out under nitrogen protection at 40-60° C. for 6-10 hours.

10. The method for preparing aluminum silicate nanofiber / acrylamide-sodium acrylate copolymer composite aerogel according to claim 8, characterized in that: In the step (3), freeze drying is to freeze dry the reaction solution at -50 to -40°C for 20 to 40 hours.

Citation Information

Patent Citations

  • Fiber reinforcement composite aerogel material and preparation method thereof

    CN112774585A

  • ZIF-8 / aluminum silicate nanofiber composite membrane and preparation method thereof

    CN119175084A